AN ANALYSIS OF TEACHERS AND STUDENTS' PERCEPTION OF ONLINE READING AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL - Misbakhul Qolby, Cepy; Agustin, Iswandini (CV RIFAINSTITUT, 2021)
This research purposes to analyze, how the teachers’ perceptions and students' perceptions of online reading in English learning. The explanation in this research is about the elements that influence online reading, the benefits of using online reading in class, and how online reading may help in the learning process, especially in reading. The questionnaire consists of fifteen statements and each statement has four alternative responses from one to four: agree, strongly agree, disagree, and strongly disagree. The questionnaire was distributed using Google Forms, and then the respondents were interviewed using WhatsApp. The results of the research indicate that teachers and the students show positive responses towards online reading. The teachers and the students perceived that online reading is ease than conventional reading. According to the research, there are benefits, including the ability for the teachers and students are to quickly find a reading topic by searching keywords, the ability for online reading to encourage students' independent learning attitudes, and students' increased interest in technology-based learning. There is one disadvantage: online reading is to be limited by the devices and tools accessible.